011 EMS crews' attitudes towards working with pre-hospital doctors in the field. Issue 3 (1st March 2011) - Lyon, Richard; Gowens, Paul; Egan, Gerry; Andrews, Peter; Clegg, Gareth
Abstract : Background: In certain European countries pre-hospital doctors attend all out-of-hospital cardiac arrests. This is not routine practice in the United Kingdom. Pre-hospital doctors can provide support, education and certain additional clinical procedures during a resuscitation attempt. Little is known about the interaction between EMS crews and pre-hospital doctors in the field. Aims: To establish the EMS crews' views, impressions and attitudes towards pre-hospital doctors immediately after an OHCA resuscitation attempt. Methods: Prospective, observational questionnaire survey. A pre-hospital doctor attends the scene of OHCA in the Lothians regions of Scotland as part of an on-going research project. After a resuscitation attempt at which the doctor was present, the attending EMS crew was invited by email to complete an anonymous, online survey on their experience with working with the doctor at the scene. Results: 68 emails were sent to EMS personnel immediately after a resuscitation attempt at which a doctor was present. 48 (71%) responses were received. All respondents felt reassured by the presence of a doctor at the scene of OHCA and all felt the doctor gave useful, real-time feedback. 16 (24%) of EMS personnel felt their own performance improved after arrival of the doctor. 44 (92%) EMS personnel found the presence of a doctor at the OHCA useful. Of the 15 that responded in the free comments section, 11 (92%) felt that on-scene training and feedback were the most useful attributes of having a doctor at an OHCA. Overall, EMS crews felt pre-hospital doctors were most useful in cases of major trauma (94%), compared to major incident (75%), cardiac arrest (75%) and paediatric emergency (58%). The majority (70%) of surveyed EMS personnel prefer pre-hospital doctors to be tasked by ambulance control directly rather than wait for an on-scene crew request. Conclusions: The presence of a pre-hospital doctor appears to be accepted by EMS personnel in this region. EMS crews value the experience of learning and gaining feedback and on-scene training from a pre-hospital doctor during OHCA resuscitation. Pre-hospital doctors can be beneficial for EMS crew training and relations as well as providing advanced medical care.